2018
DOI: 10.1111/ppc.12271
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of premenstrual and menstrual symptoms to alexithymia among nursing students

Abstract: Women should be evaluated for alexithymia to prevent the adverse effects of premenstrual and menstrual symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
(123 reference statements)
0
8
0
Order By: Relevance
“…In this context, the foremost suffering was addressed from these symptoms, which are university students. The university period may be transitional and sensitive as students cannot deal with psychological and social changes and manage the stresses of their daily lives (Öksüz and Guvenc, 2018); their primary goal is to realize higher academic achievement to secure better jobs and meet their particular needs; this makes them look for positive psychological and physical energy. However, their psychological and social situations may interfere with their ability to manage university requirements, which results in increased exposure to health and psychological pressures that negatively affects their academic performance and academic achievement (Öksüz and Guvenc, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the foremost suffering was addressed from these symptoms, which are university students. The university period may be transitional and sensitive as students cannot deal with psychological and social changes and manage the stresses of their daily lives (Öksüz and Guvenc, 2018); their primary goal is to realize higher academic achievement to secure better jobs and meet their particular needs; this makes them look for positive psychological and physical energy. However, their psychological and social situations may interfere with their ability to manage university requirements, which results in increased exposure to health and psychological pressures that negatively affects their academic performance and academic achievement (Öksüz and Guvenc, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The university period may be transitional and sensitive as students cannot deal with psychological and social changes and manage the stresses of their daily lives (Öksüz and Guvenc, 2018); their primary goal is to realize higher academic achievement to secure better jobs and meet their particular needs; this makes them look for positive psychological and physical energy. However, their psychological and social situations may interfere with their ability to manage university requirements, which results in increased exposure to health and psychological pressures that negatively affects their academic performance and academic achievement (Öksüz and Guvenc, 2018). Reports showed that from 1.8 to 5.8% of females complain of a severe sort of premenstrual symptoms (PMDD or PMS [PMS]), which restricts their social and occupational functioning (Öksüz and Guvenc, 2018;Watted et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on Turkish nursing students found that severe symptoms of menstrual discomfort resulted in a decrease in activities, an increase in tension, proneness to anger, hip and abdominal pain, backache, headache, and fatigue [3]. It even affects their alexithymia [4]. Nursing students believe that symptoms of menstruation cause not only physical discomfort and mood changes, but are also negative and limiting in that they make students feel less attractive [5].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that nursing students suffering from alexithymia have difficulty identifying emotions in social relationships, causing them to adopt avoidance modalities. 31 They generally have a higher tendency to both introspection and shyness. 32 In this regard, some studies refer to Henderson et al 21 and Weeks et al, 33 who point out that, there can be significant relationships between social identity and selfesteem, social understanding, emotional regulation, and lack of shyness.…”
Section: Introductionmentioning
confidence: 99%